2011
DOI: 10.1258/la.2010.010090
|View full text |Cite
|
Sign up to set email alerts
|

Single dose streptozotocin-induced diabetes: considerations for study design in islet transplantation models

Abstract: Streptozotocin (STZ)-induced diabetes mellitus (DM) offers a very cost effective and expeditious technique that can be used in most strains of rodents, opening the field of DM research to an array of genotypic and phenotypic options that would otherwise be inaccessible. Despite widespread use of STZ in small animal models, the data available concerning drug preparation, dosing and administration, time to onset and severity of DM, and any resulting moribundity and mortality are often limited and inconsistent. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
376
0
20

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 482 publications
(438 citation statements)
references
References 48 publications
15
376
0
20
Order By: Relevance
“…9A-C. Streptozotocin uptake via the cell membrane GLUT2 glucose transporter, causing DNA alkylation and eventual b cell death, mimics autoimmune T-lymphocytesrelated insulitis that characterizes type 1 diabetes in humans (Rossini et al, 1977;Deeds et al, 2011). The appropriateness of chemically-induced diabetes in investigations involving drug testing or in therapies working via non-beta cell dependent pathways, such as new insulin formulation tested in this study, has been widely reported (Jederstrom et al, 2005;Sheshala et al, 2009).…”
Section: In Vivo Insulin Bioactivitymentioning
confidence: 88%
“…9A-C. Streptozotocin uptake via the cell membrane GLUT2 glucose transporter, causing DNA alkylation and eventual b cell death, mimics autoimmune T-lymphocytesrelated insulitis that characterizes type 1 diabetes in humans (Rossini et al, 1977;Deeds et al, 2011). The appropriateness of chemically-induced diabetes in investigations involving drug testing or in therapies working via non-beta cell dependent pathways, such as new insulin formulation tested in this study, has been widely reported (Jederstrom et al, 2005;Sheshala et al, 2009).…”
Section: In Vivo Insulin Bioactivitymentioning
confidence: 88%
“…STZ in the dose 60-250mg/kg, body weight has been demonstrated to induce complete destruction of cells in most species within 24 hour [25], Rapid development of diabetes which many times resembles to Type 1 diabetes mellitus. Addition of Nicotinamide helps to preserve some pancreatic cells and gives the appearance of type 2 diabetes which is a well known model of Type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Sixty-eight rats were injected intraperitoneally with streptozotocin (STZ) dissolved in saline at a dose of 60 mg/kg for 5 consecutive days [12]. The development of hyperglycemia in rats was confirmed by blood glucose estimation after 11 days of first STZ injection.…”
Section: Induction Of Type I Diabetesmentioning
confidence: 99%